Strategi Pengembangan Usaha Mikro, Kecil dan Menengah (UMKM) yang Dilakukan Dinas Koperasi dan UMK Kabupaten Labuhanbatu dalam Meningkatkan Perekonomian Masyarakat Sekitar - Melisa Syafitri Amalia; Muhammad Arif (VISA: Journal of Vision and Ideas, 2022)
The purpose of this research is to develop cooperation strategies for Labuhanato Regency and the Small and Medium Enterprises Office in small business development efforts in Labuhanbato Regency during the Covid-19 pandemic. This search uses quantitaif with a descriptive approach. This type of research is field research. The results of this study in the analysis use inference methods that start with general data and end with conclusions. Based on the results of the study, it can be concluded that the strategy of small business development in Labuhanbato Regency during the Covid-19 outbreak is through a program for Micro business problem services from commercial production processes, development of promoting small business products, network improvement between institutions, micro strandarization commercial product production services. Keywords: strategy, MSME Development, Covid-19 Pandemic